2006
DOI: 10.1111/j.1600-6143.2006.01552.x
|View full text |Cite
|
Sign up to set email alerts
|

FTY720 versus MMF with Cyclosporine in de novo Renal Transplantation: A 1-Year, Randomized Controlled Trial in Europe and Australasia

Abstract: FTY720 is a novel immunomodulator investigated in de novo renal transplantation and other therapeutic areas including multiple sclerosis. This 1-year multicenter, randomized, phase III study in 668 de novo renal transplant patients compared FTY720 2.5 mg plus full-dose cyclosporine (FDC) or FTY720 5.0 mg plus reduceddose cyclosporine (RDC), with mycophenolate mofetil (MMF) plus FDC. The primary efficacy endpoint was the composite incidence of first treated biopsy-proven acute rejection (BPAR), graft loss, deat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
101
0
3

Year Published

2007
2007
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 140 publications
(106 citation statements)
references
References 17 publications
2
101
0
3
Order By: Relevance
“…This drug induces a migratory block that prevents lymphocytes from exiting the lymph nodes. A notable immunosuppressive effect could be demonstrated in human solid organ transplantation (6,7).…”
mentioning
confidence: 88%
“…This drug induces a migratory block that prevents lymphocytes from exiting the lymph nodes. A notable immunosuppressive effect could be demonstrated in human solid organ transplantation (6,7).…”
mentioning
confidence: 88%
“…The clinical trials assessing the use of fingolimod as an antirejection agent in renal transplant patients was reported by Salvadori et al 27 and Tedesco-Silva et al 28 Both these clinical trials evaluated higher-dose fingolimod (5 and 2.5 mg) in association with cyclosporine, and both reported higher rates of macular oedema (Salvadori et al: 2.2% at 5 mg dose, 1.3% at 2.5 mg dose), (Tedesco-Silva et al: 3.4% at 5 mg dose and 1.7% at 2.5 mg). Tedesco-Silva and Salvadori did not exclude patients with diabetes in the sample population.…”
Section: Fame and Its Association With Diabetesmentioning
confidence: 99%
“…25,26 Incidence of FAME Macular oedema has been a well-documented side effect of fingolimod since it was originally evaluated as an anti-rejection agent for renal transplantation. 27,28 Fingolimodassociated macular oedema was therefore monitored for and reported in the initial clinical trials investigating the efficacy of fingolimod for RRMS. The FREEDOMS study was a phase III multicentre, 24-month, double blind randomised study comparing 0.5 mg (n = 425) and 1.25 mg (n = 429) fingolimod daily treatment with placebo (n = 418) in patients with RRMS.…”
Section: Fingolimod and The Eyementioning
confidence: 99%
“…Unexpectedly, both FTY720 treatment arms were associated with lower creatinine clearance and higher incidence of macular edema. 56,57 These results, unexplained but believed to be attributable to nonimmunological renal toxicity, indicated that FTY720 provided no benefit in comparison to standard care and resulted in temporary stopping of the development of FTY720 for renal transplantation.…”
Section: Fingolimod (Fty720)mentioning
confidence: 97%